(untitled) (Revista Innova Educación, 2021)
The concept of creativity has progressed over time to become one of the fundamental human skills of this century. This study aimed to review different articles and analyze their academic contributions to creative thinking and the strategies used to promote it from primary education. The methodology used was the documentary review of 60 articles published in various reliable databases. The axes of the study proposed as conceptual definitions, characteristics of the creative student, and strategies used by teachers were taken into account. Concluding that there is a need to stimulate this thought so that students initially express their productions in the face of situations and challenges presented in daily life.